2010
DOI: 10.1016/j.jtbi.2010.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Non-local models for the formation of hepatocyte–stellate cell aggregates

Abstract: Elsevier's AAM Policy: Authors retain the right to use the accepted author manuscript for personal use, internal institutional use and for permitted scholarly posting provided that these are not for purposes of commercial use or systematic distribution. Permitted scholarly postingVoluntary posting by an author on open websites operated by the author or the author's institution for scholarly purposes, as determined by the author, or (in connection with preprints) on preprint servers. 24th March, 2014 Non-loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…There are several options for extending this work with an obvious extension being the consideration of other mechanisms, such as incorporating cell adhesion, cell death and cell processes within a developing tissue [3,7,21]. Similarly, this work has only considered cell populations composed of a single cell type; however, the formation of aggregates consisting of two or more cell types is also of interest [2,14,19,25]. A notable feature of these multispecies systems is that, depending upon the strengths of cell-to-cell attraction, different distributions of the various subpopulations are possible within the aggregates, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several options for extending this work with an obvious extension being the consideration of other mechanisms, such as incorporating cell adhesion, cell death and cell processes within a developing tissue [3,7,21]. Similarly, this work has only considered cell populations composed of a single cell type; however, the formation of aggregates consisting of two or more cell types is also of interest [2,14,19,25]. A notable feature of these multispecies systems is that, depending upon the strengths of cell-to-cell attraction, different distributions of the various subpopulations are possible within the aggregates, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of clusters or aggregates is a ubiquitous phenomenon in cell biology; examples include cultures of myxobacteria, the slime mould dictyostelium, and many other cell types grown in vitro for cancer research, studies in developmental biology, or applications in tissue engineering [1,6,14,16,18,19,25,26]. These aggregates can be produced by rapid cell proliferation [22] (as are, for example, those shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cells lose their ability to regulate genome stability which leads to further genetic changes and tumour development (Khalique et al, 2007). Over the last three decades it has been shown experimentally that tumours consist of heterogeneous populations of cells, which are the result of genetic instability (Stackpole, 1983; 3 of 36 new mathematical models of parabolic type have been derived to describe these cell-cell and cell-matrix adhesion processes (Armstrong et al, 2006;Dyson et al, 2016;Gerisch & Chaplain, 2008;Gerisch & Painter, 2010;Green et al, 2010;Painter et al, 2015). Since these models incorporate the assumption that cells at position x bind/unbind to/from other cells at position x ± s (for some s > 0 within cells sensing radius), they are generally nonlocal.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, our framework allows fibres embedded within the ECM to affect both the collagen mechanics (through the transversely isotropic form of the stress tensor) and cell-ECM interactions (though the anisotropic drag and cell-ECM force terms). The cell-ECM force is modelled via a convolution integral term, an approach which is increasingly being used to represent cell-cell and cell-ECM interactions in continuum models (Gerisch and Chaplain, 2008;Green et al, 2010;Szymanska et al, 2009). For an isotropic ECM, recent work (Green et al, 2013) has shown that, if the 'sphere of influence' of each cell is small, the nonlocal term can be approximated by the gradient of a function of cell and ECM density.…”
Section: Discussionmentioning
confidence: 99%